Collatamp sponges in the management of open fractures - Ciriello, V.; Maccauro, G.; Ziranu, et al., A. (Acta Biomedica Atenei Parmensis, 2012)
Open fractures are at high risk of infection and the prompt treatment of these injuries is critical to the success and is crucial to reduce the rate of complications. The basic steps of treatment include the immediate administration of systemic antibiotics, early surgical stabilization of the fracture associated with copious irrigation and radical debridement of the site of exposure, and when possible adequate soft tissue coverage. The systemic antibiotic therapy significantly improves the prognosis and reduces the occurrence of complications. However, in order to ensure adequate and sustained local concentration of antibiotic agent, high doses and for a long time are necessary. This increases the risk of side effects and bacterial resistance. The introduction of the antibiotic-loaded collagen sponges offers the advantages of a high local concentrations of antibiotic carrier delivering system with reduced systemic drug diffusion (less risk of side effects and resistance rate). Sponges are also biodegradable and fully resorbable and do not require additional surgery for their removal.